Case Report: An unusual case of a transposition of the great arteries with a double aortic arch: a highly complex fetal diagnosis with an unpredictable outcome - Masci, M.; Missineo, A.; Campanale, C. M.; Moras, P.; Colucci, M. C.; Pasquini, L.; Toscano, A. (Frontiers in Cardiovascular Medicine, 2024)
Published data estimate the prevalence of the vascular ring at approximately 7 per 10,000 live births. The association of a double aortic arch with a D-transposition of the great arteries has been rarely described in the literature. In this study, we report the prenatal diagnosis of a 28-year-old woman. A fetal echocardiography at a gestational age of 24 weeks + 6 days showed a D-transposition of the great arteries and a double aortic arch with a ventricular septal defect and pulmonary stenosis. On the first night after birth, the baby experienced an increase in lactate levels, with the rate of oxygen saturation consistently below 80%. A few hours after birth, the patient underwent a Rashkind procedure. An echocardiography, CT chest x-ray, and CT angiogram confirmed a diagnosis with a severe reduction of the tracheal lumen (>85%) and bronchomalacia. Then, the patient underwent posterior tracheopexy and aortopexy and later an arterial switch operation, ventricular septal defect closure, and resection of a part of the infundibular septum, accepting the risk of potential neoaortic obstruction. The literature has reported only two cases of patients with a fetal echocardiogram diagnosis. Therefore, our patient is only the third one with a fetal diagnosis and the second one with a complex intracardiac anatomy, characterized not only by a ventricular septal defect but also by two separate components of the obstruction (a bicuspid valve and a dysplastic valve with a posterior deviation of the infundibular septum). In conclusion, a D-transposition of the great arteries with a double aortic arch remains an extremely unusual association. The clinical outcome of these patients presents a high degree of variability and is entirely unpredictable in prenatal life. Our greatest aim as fetal and perinatal cardiologists is to improve the management and outcome of these patients through a fetal diagnosis, recognizing types of congenital heart disease in newborns who require early neonatal invasive procedures.